Effects of an 8-Week Active Play Intervention on Body Composition and Fundamental Motor Skills in Preschool Children - Katherine E. Spring; Danielle Lang; Melissa M. Pangelinan; Danielle D. Wadsworth (MDPI AG, 2024)
Objective: Examine the effect of an 8-week teacher-guided active play intervention on preschoolers' body composition and fundamental motor skills. Methods: Participants were from two local preschool centers randomly assigned to either the intervention (n = 25, 3.91 ± 0.53 years) or the control group (n = 25, 3.69 ± 0.81 years). All measures were assessed at baseline (week 0), post-intervention (weeks 9-11), and follow-up (weeks 30-33). Bioelectrical Impedance assessed body composition (fat mass (FM) and fat-free mass (FFM)). The Peabody Developmental Motor Scales, Second Edition (PDMS-2) assessed fundamental motor skills (gross motor quartile (GMQ)). Results: A significant Group × Time interaction for GMQ at post-intervention (p = 0.03), with the intervention group scoring significantly higher on GMQ. A significant main effect of Time (p < 0.001) indicated that GMQ increased in both groups across the 33-week period. For FM, a significant main effect of Time at both post-intervention (p < 0.05) and follow-up testing (p < 0.001) indicated that participants increased FM over the 33-week period. Lastly, there was a significant main effect of Time for FFM at post-intervention (p = 0.003) and follow-up (p < 0.001). Interestingly, there was a significant Group × Time interaction (p < 0.05) at follow-up testing showing that FFM increased over time but significantly more for the control group. Conclusions: Results indicate that active play interventions might be a successful pathway to improve gross motor skills in young children. Further research is needed to understand the effect that active play interventions have on body composition in preschoolers.